Analisis Pemanfaatan E-Learning dalam Proses Pengajaran: Studi Kasus Dosen CPNS Politeknik Negeri Bali - Putu Eka Suryadana; Ni Putu Ritra Trees Ari Kartika Hadi Saraswati; Wayan Gede Suka Parwita; I Gede Sugita Aryandana (Jurnal Media Infotama, 2025)
New lecturers at the Bali State Polytechnic can utilize a learning management system (LMS) to improve online teaching. This system supports various academic functions, such as providing access to resources, sending assignments, and creating interactive learning experiences. However, E-learning has the potential for over-reliance on technology, which can reduce traditional teaching methods and personal interaction in the classroom. This research aims to analyze the use of e-learning in the teaching process for CPNS 2024 lecturers at the Bali State Polytechnic. The research used a questionnaire with a Likert scale with a sample of 30 CPNS 2024 lecturers who had no experience as lecturers. The results of the questionnaire responses were tested for validity and reliability to ensure that the data processed was valid data. The validity test results show that all the questions tested are valid and the reliability results show a Cronbach alpha value of 0.736 and is included in the high category. Meanwhile, the results of processing the USE questionnaire by calculating the average percentage score for each factor include: usability 96%, convenience 89.5% and satisfaction 94%. A questionnaire designed to measure the usefulness of e-learning for new lecturers has proven to be valid and reliable. The results of the questionnaire show that e-learning really helps CPNS 2024 lecturers in delivering material and managing lecture assignments effectively.